Análise química de materiais argilosos e refratários modificados durante moagem por espectrometria de emissão óptica com plasma acoplado indutivamente - Santos, Mirian Cristina dos (2006)
The main goal of this thesis was the investigation of alternative procedures for chemical analysis of refractory materials and clays using an inductively coupled plasma optical emission spectrometry (ICP OES) with axial view by direct analysis of slurries and microwave-assisted alkaline digestion. The preliminary experiments of this work focused the introduction of slurries into the ICP OES with axial view and evaluated the effects caused by the particle size distribution on the intensities emission signals. Afterwards, a grinding method in which solid samples were ground together with chemical modifiers was developed. The chemical modifiers studied were LiBO2 and Na2CO3, since they are frequently used as fluxes in fusion procedures, and NH4Cl, ascorbic acid, and graphite. The effects of the chemical modification on the intensities of emission signals and the grinding time required for obtaining greater intensities emission signals were evaluated. The chemical modification procedure was implemented in order to promote the formation of new compounds with thermal properties different of the original materials. The synthesis of less refractory compounds would favor the process of atomization-excitation of the chemically modified materials in the direct analysis of slurries, and it would also facilitate the digestion of these materials. The effects of the chemical modification were also evaluated by using X-ray diffraction and thermogravimetric analysis. The direct analysis of chemically modified materials by ICP OES required the investigation of several calibration methods based on different approaches: use of aqueous reference solutions, calibration with slurries prepared using certified reference materials, and calibration using the generalized standard addition method. The calibration is the most critical aspect in the direct analysis of slurries by ICP OES, because is critically dependent on the particle sizes and of the thermal behavior of the several mineralogical phases of each material. On the other hand, microwave -assisted digestion was investigated in two alkaline media: KOH and NaOH. Applying a paired t-test it was shown that results were in agreement at 95% confidence level with those obtained by microwave-assisted acid digestion. The values of the detection limits and signal-to-background ratio obtained for the two microwave -assisted procedures were compared, and the alkaline digestion has shown adequate performance for the digestion of the chemically modified materials.